The 7th hunt - Cohen, J D; Bailey, Imogen, 1977-; Stojanovski, Jason; Charleston, Matthew; CineGear Productions (Firm); Coherent Productions (Surry Hills, N.S.W.); Leomark Studios (Firm) ([Surry Hills, N.S.W.] : CineGear Productions : Coherent Productions, 2009)
For Gothic Callie, her deaf sister Ariel, computer nerd Chris, popular Sarah, and misogynist Ricky, their evening plans are about to be re-written. Taken to an abandoned military training school, they finds themselves the target of 5 sadistic killers, each with their own unique and different style of killing. They fight for their lives against sociopaths who know their environment intimately, becoming increasingly outnumbered as their friends are killed. --
Five young friends are kidnapped and then hunted by sadistic killers.
Originally released as a motion picture in 2009
Imogen Bailey, Jason Stojanovski, Matt Charleston, Tasneem Roc, Cassady Maddox, Sarah Mawbey, Kain O'Keeffe, Darren K. Hawkings, Olivia Solomons, Malcolm Frawley, Christopher Galletti.
Cinematographer, Christopher J McHardy ; editor, JD Cohen ; music, Samantha Fonti.
In English; with optional English subtitles.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed February 8, 2018)
Keywords: Kidnapping -- Drama; Friendship -- Drama; Murder -- Drama; Fiction films; Feature films; Horror films; Thrillers (Motion pictures); Slasher films; Internet videos; Streaming video